Population synthesis with deep generative model: a joint household-individual approach - Abdoul Razac Sané; Rachid Belaroussi; Pierre Hankach; Pierre-Olivier Vandanjon (Computational Urban Science)
Abstract This paper introduces two novel deep generative frameworks for synthetic population generation that jointly model household and individual attributes. In leveraging Variational Autoencoders (VAEs), we propose herein the SVAE-Pop2 method, which employs a single VAE with fixed-size padded inputs, along with the MVAE-Pop2 method, which uses dedicated models for various household sizes. Evaluated on a French household travel survey dataset, our experiments reveal that while both approaches effectively reproduce the actual population’s characteristics, MVAE-Pop2 achieves greater fidelity in joint attribute distributions. The proposed methodologies suggest improvements in agent-based simulations and urban modeling by means of generating realistic, multi-layered synthetic populations.